Profil Kesulitan Belajar Peserta Didik dalam Memahami Materi Hidrolisis Garam - Astuti, Resti Tri (Chemistry Education Department of Education and Teaching Faculty, 2023)
Students’ result in test can be rated poorly of salt hydrolysis material showed that the student have learning difficulties. This study aimed to describe the difficulties of students and contributing factor on understanding salt hydrolysis at Madrasah Aliyah X Palembang City. The method used in this study descriptive method. This research was conducted in the second semester of the academic year 2018/2019. Subjects in this study were students of class XI MIA which consists of 76 people. Data collection techniques obtained through multiple choice test, questionnaire, and interview which was the analyzed descriptively. Based on the results of study showed that the difficulties experience by students are determine the nature of the salt hydrolysis was 56,5% with sufficient criteria. The difficulties experience by student are determine pH the salt hydrolysis was 53,29% with sufficient criteria. The difficulties experience by students are determine the equation of the salt hydrolysis was 32,89% with low criteria. The difficulties experience by student are determine the characteristics of salt hidyrolysis in water was 17,76% with very low. There are internal and external factors that cause student experience difficulties. The internal factors are lack of self-motivation and interest by students, while the external factors are the lack learning methods and questions by teacher.